2020
DOI: 10.1155/2020/7340312
|View full text |Cite
|
Sign up to set email alerts
|

Pediococcus acidilactici P25 Protected Caenorhabditis elegans against Enterotoxigenic Escherichia coli K88 Infection and Transcriptomic Analysis of Its Potential Mechanisms

Abstract: Enterotoxigenic Escherichia coli (ETEC) K88 is a zoonotic pathogen. Previous studies have shown that lactic acid bacteria (LAB) have great potential in promoting health and resisting pathogenic infections; however, relatively little research has been done on the Pediococcus genus of LAB. This study is aimed at exploring the mechanisms imparted by Pediococcus acidilactici P25 against ETEC K88 in Caenorhabditis elegans. The probiotic performance of P25 was investigated in vitro. Colonization of K88 in the intest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 82 publications
0
12
0
1
Order By: Relevance
“…C-type lectins have been reported to be involved in serum glycoprotein homeostasis, pathogen detection, and initiation of an immune response ( Mayer et al., 2017 ). UDP-glucuronyl transferase (UGT) and cytochrome P450 are involved in chemical detoxification and innate immune responses ( Simonsen et al., 2012 ; Tan et al., 2020 ). Tan et al.…”
Section: Resultsmentioning
confidence: 99%
“…C-type lectins have been reported to be involved in serum glycoprotein homeostasis, pathogen detection, and initiation of an immune response ( Mayer et al., 2017 ). UDP-glucuronyl transferase (UGT) and cytochrome P450 are involved in chemical detoxification and innate immune responses ( Simonsen et al., 2012 ; Tan et al., 2020 ). Tan et al.…”
Section: Resultsmentioning
confidence: 99%
“…Park et al (38) reported that probiotic L. fermentum strain JDFM216 stimulated the longevity and immune response of C. elegans through a nuclear hormone receptor (NHR) family and PMK-1 signaling (38). Pediococcus acidilactici P25 strain affected expression of the genes related to innate immune response and upregulated the abundance of transcripts in multiple pathways of C. elegans, including peroxisome, longevity, and MAPK pathways (42). Nevertheless, these reports have not yet identified immunomodulatory effects of Lactobacillus on the targeting sites downstream of the p38 MAPK and DAF/IGF pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of mutations in different genes associated with the responses have identified downstream proteins involved in pathogen defense, such as LYS (lysozyme) family, ABF ( Ascaris suum antibacterial factor) family, SPP (Caenopores are the saposin-like proteins) family, and C-type lectins family ( 29 , 30 ). However, the role of these antimicrobial peptides in response to bacterial infection is yet to be fully elucidated ( 7 , 14 , 42 ). In the present study, the transcription of genes that encode for antimicrobial peptides including abf-3, lys-7 , and spp-1 was all significantly upregulated in the WT nematode when it was exposed to DT104.…”
Section: Discussionmentioning
confidence: 99%
“…Tan et al . (2020) explored the mechanism of inhibitory effect of P. acidilactici P25 on enterotoxigenic Escherichia coli K88, and the co‐culture results showed that the presence of P25 significantly inhibited the growth of E. coli K88. Therefore, in A3 period, Pseudomonas_sp._GR7 may be inhibited by P. acidilactici so that the abundance decreased to a very low level.…”
Section: Resultsmentioning
confidence: 99%